ІНВЕСТИЦІЙНІ РИЗИКИ СТРАХОВИХ КОМПАНІЙ КРІЗЬ ПРИЗМУ ВІТЧИЗНЯНОЇ ПРАКТИКИ (Світ фінансів, 2017)
Письменна Т. В. Інвестиційні ризики страхових компаній крізь призму вітчизняної практики. Розкрито суть інвестиційного ризику страхової компанії. Виокремлено наукові позиції стосовно визначення місця інвестиційної діяльності страхової компанії поряд з її страховою діяльністю. Дано характеристику агресивної, консервативної та помірно-консервативної інвестиційних стратегій страхових компаній. Проаналізовано основні показники інвестиційної діяльності українських страхових компаній. Визначено види ризиків в інвестиційній діяльності страхової компанії. Запропоновано основні методи нейтралізації інвестиційних ризиків страхової компанії. Письменная Т. В. Инвестиционные риски страховых компаний через призму отечественной практики.Раскрыта сущность инвестиционного риска страховой компании. Выделены научные позиции относительно определения места инвестиционной деятельности страховой компании рядом с ее страховой деятельностью. Дана характеристика агрессивной, консервативной и умеренно-консервативной инвестиционных стратегий страховых компаний. Проанализированы основные показатели инвестиционной деятельности отечественных страховых компаний. Определены виды рисков в инвестиционной деятельности страховой компании. Предложены основные методы нейтрализации инвестиционных рисков страховой компании. Pysmenna T. Investment risks of insurance companies through the prism of domestic practice.Introduction. In modern conditions insurance companies has engaged in investment activity under various risks. Management of insurance company can’t influence the market risks. Insurance company can apply the methods of risk management in investment activity.Purpose. The purpose of scientific research is to find out the essence and composition of investment risks of insurance company.Results. The essence of the investment risk of insurance company is found out. The position of investment activity of insurance company along insurance activity under different scientific views is determined. Aggressive, conservative and moderately conservative investment strategies of insurance companies are characterized. The main indicators of investment activity of domestic insurance companies are analyzed. The types of investment risk of insurance company are determined. The main methods of neutralizing the risk of investment activity of insurance company are established.Conclusion. It is concluded that the essence of the investment risk of insurance company belongs to a number of controversial ones. Established, that insurance and investment activities of insurance company are closely linked. It has been found, that aggressive, conservative and moderately conservative investment strategies of insurance companies are different levels of profitability and risk of funds allocation. Over the last years the investment activity of domestic insurance companies showed almost stable positive results. Summarized, that investment risks, associated with incompetent management, the most threaten to insurance company. Avoidance, limitation and diversification are the main methods of neutralizing the risks in investing activity of insurance companies.